Statute of limitation of labor actions: substance and form issues - Toledo Filho, Manoel Carlos (2013)
This study aims to place the statute of limitation legal definition in the general context of labor law analyzing its compatibility with fundamental precepts of that specific legislation area: identifying also features, boundaries and deadlines adopted by Ibero-American countries, mainly members of the southern cone.